Customer Data Protection by Bank Rakyat Indonesia is Reviewed by Law Number 27 of 2022 Concerning Personal Data - Negoro, Della Gatiko; Purwanto, Gunawan Hadi (IHSA Institute, 2024)
This research aims to determine the suitability of Bank Rakyat Indonesia's form of personal data protection for customers in accordance with Law Number 27 of 2022 concerning Personal Data Protection. Individuals and community groups take advantage of the lack of boundaries between public space and privacy to operate and seek profits via the Internet, giving birth to a phenomenon known as cybercrime, one of which is the violation and theft of personal information. The research method used is normative-empirical legal research. Data sources come from primary legal materials and secondary legal materials. Qualitative data analysis techniques are presented descriptively. The result is that the right to privacy is part of human rights which is specifically protected by the Personal Data Protection Law no. 27 of 2022 as a response to developments in technology, information and communication. The aim of enacting the Personal Data Protection Law Number 27 of 2022 is to protect and guarantee the basic rights of citizens in protecting the privacy of personal data. Then, the substantive framework of the Personal Data Protection Law Number 27 of 2022 is also in line with the right to privacy and the values ??contained in the philosophy of Indonesian society. Law Number 27 of 2022 concerning Personal Data Protection is expected to guarantee comprehensive protection and prevent illegal activities against the personal data of Indonesian citizens